Three dimensional primary cultures for selecting human breast cancers that are sensitive to the anti-tumor activity of ipatasertib or taselisib in combination with anti-microtubule cytotoxic drugs. (October 2018) - Orditura, M.; Della Corte, C.M.; Diana, A.; Ciaramella, V.; Franzese, E.; Famiglietti, V.; Panarese, I.; Franco, R.; Grimaldi, A.; Lombardi, A.; Caraglia, M.; Santoriello, A.; et al.
Abstract: Two inhibitors of phosphatidylinositol 3-kinase (PI3K) pathway taselisib, targeting the mutant PI3K-subunit-alpha (PI3KA) and ipatasertib, AKT-inhibitor, are currently under clinical investigation in breast cancer (BC) patients. We have previously demonstrated the anti-tumor efficacy of these anti-PI3K/AKT-inibitors in combination with anti-microtubule drugs in human BC cell lines, through a complete cytoskeleton disorganization. In this work, we generated ex-vivo three-dimensional (3D) cultures from human BC as a model to test drug efficacy and to identify new molecular biomarkers for selection of BC patients suitable for anti-PI3K/AKT-inibitors treatment. We have established 3D cultures from 25/27 human BC samples, in which the ability of growth in vitro replicates the clinical and biological aggressiveness of the original tumors. According to the results of next generation sequencing analysis, a direct correlation was found between PI3KA mutations and the sensitivity in 3D models in vitro to taselisib and ipatasertib alone and combined with anti-microtubule agents. Moreover, mutations in HER and MAPK families related genes, including EGFR, KRAS and BRAF, were found in resistant samples, suggesting their potential role as negative predictive factors of response to these agents. Thus, we demonstrated that ex vivo 3D cultures from human BC patients allow a rapid and efficient drug screening for chemotherapies and targeted agents in genetically selected patients and represent an innovative model to identify new biomarkers of drug resistance. Highlights: PI3K/AKT inhibitors exert synergistic antitumor activity with anti-microtubule drugs in breast cancer ex vivo 3D-cultures. The presence of PI3K-alpha subunit mutation correlates with sensitivity in 3D models in vitro to taselisib and ipatasertib alone and combined with anti-microtubule agents. Breast cancer ex vivo 3D-cultures represent an innovative model for an efficient drug and biomarkers screening.